Cyberchondria, but not preventive behavior, mediates the relationship between fear of COVID-19 and somatic burden: Evidence from Russia - Zolotareva, Alena (Frontiers in Psychiatry, 2022)
Background: There is extensive available research on the relationship between fear of COVID-19 pandemic and physical symptoms. This study was the first to examine the cyberchondria and COVID-19 preventive behavior as mediators of this relationship. Methods: A cross-sectional study was conducted from October to December 2021, during the fourth wave of the COVID-19 pandemic in Russia. The participants were 2,011 Russian-speaking volunteers aged 18 years and older. They completed questionnaires on somatic burden, cyberchondria, COVID-19 preventive behavior, and fear of COVID-19 pandemic. Results: Fear of COVID-19 positively predicted somatic burden, cyberchondria, and COVID-19 preventive behavior. Mediation analysis showed that the relationship between fear of COVID-19 pandemic and somatic burden was mediated by cyberchondria, but not COVID-19 preventive behavior. Conclusion: The findings suggest that cyberchondria has negative effects on somatic burden during the COVID-19 pandemic. The knowledge of the mediating role of cyberchondria may be used by health care workers when consulting persons with physical health complaints and psychosomatic disorders.